Augmented Reality Facilitates Students’ Learning in Pandemic Times of Crisis in Higher Education - Alqahtani, Ebtisam (Advances in Social Sciences Research Journal, 2023)
Teaching and learning activities swiftly transitioned to remote modes as an urgent response to the situation crisis, of the COVID-19 pandemic. The reliance on advanced technology to facilitate teaching and learning has become increasingly vital, making it important to understand the perspectives of academic staff regarding Augmented Reality (AR) as one of the advanced technologies that could address these needs. This paper aims to explore the viewpoints of academic staff regarding the use of AR facilities in higher education. To achieve this goal, a quantitative research approach was employed. The research methodology involved administering a questionnaire to gather responses from academic staff experiencing health restrictions due to the ongoing pandemic. The questionnaire used in this study was the Instructional Survey, a research tool specifically designed to elicit insights into the perspectives and opinions of academic professionals. the questionnaire was distributed to academic staff members across various faculties at five universities in Saudi Arabia, the response was from 851 academic staff. The study’s findings show a consensus among academic staff members, indicating that they agree on the potential of AR to enhance teaching and learning activities. This alignment of perspectives underscores the significance of AR in the context of higher education. his research provides valuable insights into the perspectives of academic staff during a time of crisis and their recognition of AR as a valuable tool for teaching and learning. Additionally, the study identifies areas of interest for future research, suggesting potential avenues for further exploration and investigation